SIGNS OF PETER PAN SYNDROME IN SEVERAL NIKI’S SONGS - Wijoyokusumo, Basworo; Rahayu Puji Haryanti (English Literature Department, Faculty of Economics, Law, and Humanities, 2025)
This study explores the intersection of Peter Pan Syndrome, a psychological phenomenon marked by emotional immaturity and reluctance to embrace adult responsibilities, with themes of anxiety and loneliness as reflected in the music of Indonesian singer-songwriter NIKI. By focusing on five selected songs (Pandemonium, 24, Heirloom Pain, Nothing Can, and Split), the research delves into how her lyrics articulate the emotional complexities of emerging adulthood, including self-doubt, identity struggles, and the pressures of societal expectations. Using thematic and figurative language analysis within a qualitative framework, the study examines the resonance of NIKI’s music with young listeners experiencing quarter-life crises and the broader implications of these struggles in contemporary society. Findings reveal how NIKI’s music portrays the psychological impact of anxiety and loneliness associated with Peter Pan Syndrome, offering not only a reflection of these challenges but also a message of resilience and emotional healing. By bridging psychological theory and popular culture, this research highlights the role of music as a medium for understanding and addressing modern developmental struggles.